2020
DOI: 10.1109/access.2020.3005439
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Controller Design of a DC-DC Converter for PEMFC

Abstract: Proton Exchange Membrane Fuel Cell (PEMFC) is difficult for application because of its high current and wide voltage output. A fractional order PID controller is introduced to a Four-Switch Buck-Boost DC/DC converter to stabilize the power output in this paper. To reduce the inductor current ripple, a kind of dual-triggered switch strategy is employed in detail, and an accurate dynamic model of DC/DC converter is proposed for fuel cell measurement and control system. Then a fractional order PID controller is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…The driving signals of switches S 1 and S 2 adopt dual‐triggered strategy in which the two switches are modulated at the leading edge and trailing edge, respectively 39 . In order to simplify the analysis of operational principle, the following assumptions are given.…”
Section: Theoretical Analysis and Simulation Of The Proposed Convertermentioning
confidence: 99%
“…The driving signals of switches S 1 and S 2 adopt dual‐triggered strategy in which the two switches are modulated at the leading edge and trailing edge, respectively 39 . In order to simplify the analysis of operational principle, the following assumptions are given.…”
Section: Theoretical Analysis and Simulation Of The Proposed Convertermentioning
confidence: 99%
“…The different classifications of FCs are made based on the employed electrode type [5]. One promising kind of FCs is the proton exchange membrane FC (PEMFC) technology, which possesses improved efficiency [6]. Thence, PEMFCs have been preferred as energy supply alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Although these controllers are especially sensitive when they face a large load variation, results showed a gradual and smooth rise to the desired operating power point with an acceptable tracking performance. To increase the robustness of the PID and obtain a better dynamic performance, various research groups/researchers [11] have applied a fractional order proportional integral derivative (FOPID) controller to a DC-DC four-switch buck-boost (FSBB) converter used in a PEMFC power system. The obtained results have shown that the proposed method achieved better performance in comparison with the integer-order and Two-Zero/Three-Pole (TZTP) controller.…”
Section: Introductionmentioning
confidence: 99%